The Current Consolidated Financial Statements Need to be Revised - Misirov Komoliddin Mamasabirovich; Ganiev Shahriddin Vohidovich (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2024)
This article covers aspects related to increasing investment attractiveness and reporting transparency in the preparation of consolidated financial statements in joint-stock companies based on international standards of financial statements. The organizational and methodological aspects of the preparation of consolidated financial statements in accordance with the international standards of financial statements are revealed, paying attention to the elements of the report on the statement of financial position, profit and loss and cash flow.